Sports funding for Western volleyball clubs from the perspective of industry leaders - tahar, Tahar (sports creativity, 2025)
This research aims to understand the reality of sports funding and the role played by public and private economic institutions in financing volleyball clubs in the western region. The survey method was used, and the study was applied to a sample of western clubs participating in the national championship. Data was collected through questionnaires and personal interviews with sports club managers, heads of municipal and provincial funds, and heads of youth and sports directorates, in addition to interviews with the president of the regional volleyball league and the president of the provincial volleyball league for the provinces of Oran and Mostaganem.